1966
DOI: 10.1161/01.res.18.6.683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulmonary Artery Ligation on Pulmonary Surfactant and Pressure-Volume Characteristics of Dog Lung

Abstract: The surface tension of extracts from normal lungs is extremely low owing to the presence of a specific surfactant. 1 Experiments of Finley et al. 2 showing an abnormally high surface tension of lung extracts obtained 12 to 16 hours after ligation of the pulmonary artery (PA) were confirmed by Long and associates. 3 These studies suggested that the surfactant is decreased or absent after PA ligation.The present studies were designed to correlate the pressure-volume characteristics of the lung with changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

1967
1967
1995
1995

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
(8 reference statements)
0
8
0
1
Order By: Relevance
“…2) (8). Although this observation was confirmed by other investigators (9,10,30), it subsequently has been shown that blood or plasma also impairs the surface tension lowering capabilities of normal lung extracts (11,12). Subsequently, deflation pressure volume curves, alveolar bubble stability, and phospholipid contents were shown to be normal in morphologically normal regions of dog lungs with PAO (13,14).…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…2) (8). Although this observation was confirmed by other investigators (9,10,30), it subsequently has been shown that blood or plasma also impairs the surface tension lowering capabilities of normal lung extracts (11,12). Subsequently, deflation pressure volume curves, alveolar bubble stability, and phospholipid contents were shown to be normal in morphologically normal regions of dog lungs with PAO (13,14).…”
Section: Introductionmentioning
confidence: 56%
“…As the duration of occlusion increases, the addition of CO2 to the inspired gas is no longer capable of reversing the decrease in compliance and ventilation to the occluded lung (8). This irreversibility coincides with the development of atelectasis, hemorrhage, and edema in the occluded lung, which in turn has been attributed to loss ofthe alveolar surface lining material, surfactant (8)(9)(10). Although the ability of pulmonary surfactant to reduce surface tension is decreased after pulmonary artery occlusion, it remains unclear whether this alteration in function contributes to the development or results as a consequence of the alveolar edema and hemorrhage that occur (8,(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The length of time that hypocapnic bronchoconstriction persists after ligation is unknown, but it probably depends on the speed and extent of neovascularization of the lung by bronchial collaterals [3]. Of greater importance, within 2 days of ligation areas of the affected lung become atelectatic and its total lung volume is reduced by 40-50% [11,19,20]. The proportion of total ventilation directed to that lung is probably reduced below 30%, but no data are available in the literature for this postligation time period.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has been a useful experimental model for the study of altered pulmonary surface activity (6)(7)(8). Our aims were to: (1) localize the distribution of surface activity in the supernatant and sedimentary fractions of the wash fluid from lungs; (2) correlate the lipid composition of these fractions with their relative surface activity; (3) assess the possible role of the alveolar cells in synthesizing or storing sur-…”
Section: Introductionmentioning
confidence: 99%